Literatura Premiada: Possibilidades de Diálogo com o Público Adolescente - Johann, Gisela (2017)
This master thesis is based in the study of the possibilities for dialogue between award-winning Youth Literary by the National Foundation of Infantile and Juvenile Book – NFIJB – and teen audience, whom these books are intended. Since 1975 the NFIJB selects books that are deserving of Highly Recommended Stam, thus, it is analyzed in this research to those awarded between 2010 and 2014: A espada e o novelo (Dionisio Jacob); Uma ilha chamada livro: contos mínimos sobre ler, escrever e contar (Heloisa Seixas); Com certeza tenho amor (Marina Colasanti); Marginal à esquerda (Angela Lago); Querida (Lygia Bojunga); O tempo de voo (Bartolomeu Campos de Queirós); O Mururu no Amazonas (Flávia Lins e Silva); A morena da estação (Ignácio de Loyola Brandão); Aquela água toda (João Anzanello Carrascoza); Aos 7 e aos 40 (João Anzanello Carrascoza). In fact, to identify such aspects of dialogue (reader-book), this work will consider Literature as a social object, in this way, the reader becomes an essential part for the text to come to life. As a theoretical support, concepts and discussions of the Sociology of Reading, Bauman's (2009) studies of Net Modernity and, also, the model reader concepts of Umberto Eco (1994), from what the works under study presuppose of their expected reader. Thus, this study also seeks to indicate the relevance of the sociocultural aspects imbricated in the construction of this model reader.